Custom abutments on tilted implants in the maxilla: A clinical report - Fabrizio Di Francesco; Gennaro De Marco; Attilio Sommella; Alessandro Lanza (Wolters Kluwer Medknow Publications, 2020)
The aim of this work is to describe a case of severe disparallelism between two implants supporting a cement-retained bridge, placed in the maxilla, employing two custom-angled abutments. Fractured abutment screw and fractured abutment involved two implant restorations in the maxilla. Once prosthetic components have been removed, a new prosthetic rehabilitation has been planned. The divergence between the implants was measured, obtaining an angle of divergence of 39°. Then, two custom-angled titanium abutments and two metal-ceramic splinted crowns were realized.